Anti-obesity effects of artificial planting blueberry (Vaccinium ashei) anthocyanin in high-fat diet-treated mice. (2nd April 2016) - Wu, Tao; Jiang, Zenghong; Yin, Jinjin; Long, Hairong; Zheng, Xiaodong
Abstract: This study aimed to evaluate the anti-obesity effects of artificial planting blueberry ( Vaccinium ashei ) anthocyanin (BA) in high-fat diet-induced obese male C57BL/6 mice. BA at doses of 50, 100, and 200 mg/kg was supplemented in the daily food of obese C57BL/6 mice during an 8-week experiment. Our findings indicate that consumption of BA at high doses reduced body weight by 19.4%, whereas both low and middle doses did not affect the body weight. Furthermore, BA supplementation at high dose could effectively decrease serum glucose, attenuate epididymal adipocytes, improve lipid profiles, and significantly down-regulate expression levels of TNFα, IL-6 PPARγ, and FAS genes. Therefour, BA might alter bodyweight by suppressing fatty acid synthesis and alleviating inflammation.